Psychometric properties of the MESSY Scale (self-assessment) in Argentinean children - Ipina, Maria Julia (2011)
This study examines the psychometric properties of the Matson Evaluation of Social Skills with Youngsters (Matson, Rotatori & Helsel, 1983), which assesses specific social skills involved in adaptive and non-adaptive behaviors. The factor structure and internal consistency were studied in a sample of children from Cordoba (n = 578) of 7 to 13 years old (M = 9.48, SD = 1.47) of both sexes (52.77% males). An exploratory study of data and variables was conducted; then the factor structure was studied. Results suggest that the structure of five factors was the simplest and theoretically most consistent: Aggressiveness/Antisocial Behavior, Appropriate Social Skills, Friendship, Overconfidence/Jealousy/Pride and Loneliness/ Social Anxiety. The internal consistent coefficients were good or acceptable in most dimensions. Gender differences observed in the dimensions and total score provide evidence of the validity of the instrument.